Triggered intracellular activation of disulfide crosslinked polyelectrolyte gene delivery complexes with extended systemic circulation in vivo. - Oupický, D; Carlisle, R; Seymour, L (Springer Nature, 2001)
We have developed polyelectrolyte gene delivery vectors that display good extracellular stability and are activated intracellularly to permit transgene expression. The strategy comprises covalent crosslinking of primary amines in poly-L-lysine/DNA complexes with a crosslinking agent that can later be cleaved by reduction. Crosslinked complexes maintained the same size and surface charge but showed increased stability against polyelectrolyte exchange with poly-L-aspartic acid. Surface modification with polyethyleneglycol improved solubility and masked their positive surface charge. Crosslinked complexes showed 10-fold increased plasma circulation following intravenous administration to Balb/c mice. In the absence of chloroquine, the levels of transgene expression in B16F10 murine melanoma cells were similar for crosslinked and non-crosslinked complexes, however, chloroquine selectively potentiated transgene expression by the non-crosslinked complexes. Cellular uptake of the complexes was the same, irrespective of crosslinking. Following microinjection into the cytoplasm of Xenopus oocytes, or the cytoplasm or nucleus of Rat-1 fibroblasts, crosslinked complexes mediated the same transgene expression as non-crosslinked complexes, indicating crosslinked complexes are rapidly reduced and activated intracellularly. We therefore hypothesize that the lower in vitro transfection activity of crosslinked complexes in the presence of chloroquine is due to reduced transfer from endosome to cytoplasm, mainly due to increased stability against destabilization by chloroquine. The extended systemic circulation together with triggered intracellular activation makes these complexes a promising system for targeted gene delivery in vivo.